Paediatric Traumatic Endophthalmitis in Western India: A Study of Clinical Presentation, Management, and Treatment Outcomes - Shah, Shreya; Shah, Mehul; Vador, Raj; Rajoria, Vedant; Shah, Riddhi; Chandana, Bhoomi; Tiwari, Deepak (British Journal of Healthcare and Medical Research, 2025)
Introduction: Endophthalmitis is a devastating sight-threatening condition following open globe injury. The study aims to determine the rate of endophthalmitis and assess risk factors for the development of endophthalmitis following open globe injury (OGI). Methods: A retrospective review of all children treated for OGI at the Drashti Netralaya from January 2008 to December 2022 was conducted according to predefined inclusion and exclusion criteria. The main outcome measures were the rate of endophthalmitis, different variables, and visual outcome. Result: In this study, 53/1551 (3.42%) eyes had endophthalmitis. Cross-tabulation and descriptive analyses identified presenting vision (0.012), corneal condition (0.009), vitreous opacities (0.000), and age group (0.003) as high-risk factors of developing endophthalmitis. The type of interventions and subconjunctival antibiotic injection at the time of globe closure (0.011) was associated with a decreased risk of developing endophthalmitis. Conclusion: Careful aggressive management according to clinical findings, has a statistically significant impact on the visual outcome even in the pediatric age group.